(untitled) (Sustainability in Debate, 2013)
This article, presented in the form of an essay, seeks to bring to the debate several elements of suspicion regarding the current models of sustainability, as an expression of wider frames inscribed on the modernity crisis. The article analyses the extent and the logics of the construction of sustainable tourism discourses in the light of the analytic contamination of such models. The construction of the concept of sustainability, when put into perspective between the concepts of technological operativism and political decisionism and articulated with the triple axis of preservation-tourism-consumption, puts into question the nature of many of the figurative and refigurative strategies for tourism. Those strategies seek to take tourism as a catalyst for the stimulation of local economies preserving - at the same time- culture and environment.